Looking South: What can Youth Studies in the Global North learn from research on youth and policy in the Middle East and North African countries?. Issue 3 (27th May 2021) - MacDonald, Robert; King, Hannah
ABSTRACT: Connell's 'Southern Theory' calls for intellectuals in the 'Global North' 'to start learning in new ways, and in new relationships' with and from scholars in the 'Global South' in order to better understand the subjects of our research. This, exactly, is the motivation of this paper. In working with, and drawing, on a large, comparative research programme about young people and youth policy in some of the Middle East and North African (MENA) countries (the POWER2YOUTH research project), we explore what can be learned for sociologically-oriented Youth Studies in the 'Global North' through collaborative research in the 'Global South'. The paper brings together research and theory from different disciplines/fields as well as from different regions/states so as to consider how we might better research and theorize about 'youth' (as a socially constructed life-phase) and about the empirical realities of young people's lives (as they play out in social, political, cultural and economic contexts). Consequently, the paper discusses five themes or issues that we see as important for Youth Studies in the 'Global North': the variation in dominant state/social constructions of 'youth'; the plurality of social divisions amongst youth; the different meanings of insecurity for young people; the flaws in human capital-based youth policies; and the significance of informal and non-standard work for young people. In conclusion, we summarize our arguments and underscore the value of a political economy perspective in Youth Studies.